The Effectiveness of The Use of Antihyperuricemia Against Decrease In Uric Acid Levels In Hypertensive Patients With Gout at Puskesmas X Rembang Regency - Indah Wahyu Setianingsih; Endang Setyowati; Intan Adevia Rosnarita (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to evaluate the effectiveness of the use of antihyperuricemic drugs in reducing uric acid levels in hypertensive patients who also suffer from gout at Community Health Center 1 Rembang. This type of research is a quantitative study with a cross-sectional design, using secondary data from medical records from 2024–2025. In this study, there were 91 respondents who met the inclusion criteria. The dominant characteristic of the respondents was men aged 51–65 years with an educational background ranging from elementary to junior high school. The most commonly used antihypertensive drug was amlodipine (85.7%). Before undergoing therapy, all patients (100%) showed abnormal blood pressure levels. After antihypertensive therapy, 45 patients (49.5%) had normal blood pressure, while 46 patients (50.5%) were in the abnormal category with amlodipine in 78 patients (85.7%) and captopril in 11 patients (12.1%), while the most common antihyperuricemic drug was allopurinol (87.9%). Before undergoing therapy, all patients (100%) showed abnormal uric acid levels. After antihyperuricemic therapy, 23 patients (25.3%) managed to achieve normal uric acid levels, while 68 patients (74.7%) remained in the abnormal category. Bivariate analysis showed that the average uric acid level before therapy was 8.9 mg/dL, which decreased to 7.3 mg/dL after therapy, with an average decrease reaching 1.6 mg/dL. Paired t-test indicated a p value = 0.000 (p < 0.05), indicating a significant difference between the conditions before and after therapy. In conclusion, the application of antihyperuricemia has been proven effective in reducing uric acid levels in patients with hypertension who also have gout at Community Health Center 1 Rembang.